Bridging the Terahertz Gap: Channel Modeling for Next-Generation 6G Wireless Networks - A. Sohoo, Arslan; C. Seman, Fauziahanim; S. Khee, Yee; A. Sohu, Izhar; S. Ishak, Nurul; H. Ikhsan, Fatin
The THz spectrum (0.1–10 THz) is a region between optics and electronics, and it is still not fully explored and is unlicensed. Recent studies show that it will bring a revolution in technology, especially in the field of communication. Future communication technologies such as 6G and Terabit DSL will utilize this THz band as it has the capability to support high data rates in Tbps. For designing an efficient system that propagates these THz waves with low loss, it is required to understand the propagation channel properly. THz channel modeling is at its infancy stage, and a detailed investigation of channel behavior is required to study the efficient propagation of THz waves. In this study, the methods applied to the modeling of the THz channel are discussed in detail. Although channel modeling is a broad topic here only the methods and techniques are discussed along with their advantages and limitations. Lastly, the challenges and the future direction in the field of THz channel modeling are also discussed.